Empreendimentos costeiros de grande porte e conflitos no uso e ocupação do solo : a zona costeira Sul capixaba - Bitencourt, Christianne Provietti (2013)
This paper analyzes the changes in the coastal zone from the installation of port structures and its empirical object the southern coast of Espírito Santo limited by the municipalities of Anchieta, Piuma, Itapemirim Marataízes and President Kennedy. The r